2018
DOI: 10.1186/s13014-018-1061-7
|View full text |Cite
|
Sign up to set email alerts
|

Dose constraints in the rectum and bladder following carbon-ion radiotherapy for uterus carcinoma: a retrospective pooled analysis

Abstract: BackgroundCarbon-ion radiotherapy (C-ion RT) provides better dose distribution in cancer treatment compared to photons. Additionally, carbon-ion beams provide a higher biological effectiveness, and thus a higher tumor control probability. However, information regarding the dose constraints for organs at risk in C-ion RT is limited. This study aimed to determine the predictive factors for late morbidities in the rectum and bladder after carbon-ion C-ion RT for uterus carcinomas.MethodsBetween June 1995 and Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…From NIRS NTCP analysis, the rectum appears as a serial organ regarding late complications, in agreement with conclusions from Okonogi et al [17] Therefore, in the definition of updated constraints, focus was given to high rectum doses. The new values were expressed in cc to overcome the previously discussed differences determined by rectum size variation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…From NIRS NTCP analysis, the rectum appears as a serial organ regarding late complications, in agreement with conclusions from Okonogi et al [17] Therefore, in the definition of updated constraints, focus was given to high rectum doses. The new values were expressed in cc to overcome the previously discussed differences determined by rectum size variation.…”
Section: Discussionsupporting
confidence: 86%
“…Taking these uncertainties into account, the estimated probability of late rectal complications was very low. In Okonogi et al, D MKM|2cc was found to be the most significant predictive factor for late rectal morbidities, with a threshold of 57.3 Gy(RBE) to limit the risk for a 20 fraction treatment schedule [17]. Under the hypothesis that schedules could be compared based on the biological effective dose (BED) concept, the corresponding 16 fraction threshold value, assuming an α/β ratio of 3.9 Gy for the rectum [25], would be 53.5 Gy(RBE).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We previously reported that the minimal clinical doses for most irradiated volumes of 2 cm 3 (D 2cc ) is a prognostic factor of late rectal complications [23]. The patient cohort was basically the same as that used in this prior study.…”
Section: Data Collectionmentioning
confidence: 99%
“…To date, several studies have reported the incidence of late morbidities after C-ion RT for pelvic malignancies [10]. We previously reported dose constraints in the rectum and bladder for C-ion RT for UC [18]. However, to the best of our knowledge, there is little information on PIF after C-ion RT for UC.…”
Section: Introductionmentioning
confidence: 99%